Investment in Social Marketing Campaign to Reduce Stigma and Discrimination Associated with Mental Illness Yields Positive Economic Benefits to California - Ashwood, J. Scott (RAND Corporation, 2016)
This report examines the potential impact of the California Mental Health Services Authority's stigma and discrimination reduction social marketing campaign on the use of adult behavioral health services, and it estimates the benefit-cost ratios.